(untitled) (Global Journal of Science Frontier Research, 2025)
This paper presents a reflective condensation of the 2025 White Paper commissionedfor the three year Galileo Commission Worldviews Study. This explored the emergence of a Unitive Worldview and Narrative as an integrative response to the metacrisis-a convergence of ecological, social, epistemic, and existential breakdowns facing humanity. Building on the legacy of the Integrative Worldview suggestion that was explored in Year One, the paper sought to advance the discussion by weaving together insights from developmental psychology, systems thinking, Indigenous cosmologies, spiritual philosophy, quantum science, and regenerative design. It proposed that the Unitive Worldview represents an evolutionary synthesis: one that transcends fragmentation and dualism by recognizing the relational, participatory, and co-creative nature of reality. Within this frame, flourishing is not merely an individual or material pursuit, but a systemic condition rooted in coherence-between self and other, society and ecology, inner life and outer systems.